Di-Cavitary Twin Pregnancy in Didelphys Uterus with Associated Renal Agenesis - Woolcock Martinez, Helen; Haghighi, Noora; Booker, Whitney A. (American Journal of Perinatology Reports, 2025)
A didelphys uterus is a rare Müllerian duct anomaly (MDA) caused by the incomplete fusion of the Müllerian ducts, leading to the formation of two distinct uterine cavities. The occurrence of simultaneous twin pregnancies, with each fetus developing in a separate horn of a didelphys uterus, is estimated at approximately 1 in 1,000,000 cases. This case report describes a rare instance of a spontaneous dichorionic diamniotic twin pregnancy, with one fetus in each horn of a didelphys uterus.This is the case of a 35-year-old woman with unilateral renal agenesis who presented with a spontaneous dichorionic diamniotic twin pregnancy, with one fetus in each uterine cavity. This patient's pregnancy complications included intrahepatic cholestasis of pregnancy and rising creatinine levels, leading to a planned cesarean delivery at 36 weeks. The delivery was complicated by intrapartum hemorrhage and the postpartum course was further complicated by sepsis and endometritis.This case highlights the complexity of managing a dichorionic diamniotic twin pregnancy in a didelphys uterus with concomitant congenital unilateral renal agenesis. It contributes to the understanding of optimal management strategies for MDA presentations and highlights the necessity for ongoing research into complications and long-term outcomes associated with such anomalies.
Keywords: twin pregnancy; uterus didelphys; Müllerian duct anomaly; renal agenesis